Efficacy of Tai Chi and qigong for the prevention of stroke and stroke risk factors: A systematic review with meta-analysis - Lauche, Romy (Medicine (Baltimore), 2017)
BACKGROUND: This review aims to summarize the evidence of Tai Chi and qigong interventions for the primary prevention of stroke, including the effects on populations with major stroke risk factors. METHODS: A systematic literature search was conducted on January 16, 2017 using the PubMed, Scopus, Cochrane Library, and CINAHL databases. Randomized controlled trials examining the efficacy of Tai Chi or qigong for stroke prevention and stroke risk factors were included. Risk of bias was assessed using the Cochrane Risk of Bias tool. RESULTS: Twenty-one trials with n = 1604 patients with hypertension, hyperlipidaemia, diabetes, overweight or obesity, or metabolic syndrome were included. No trials were found that examined the effects of Tai Chi/qigong on stroke incidence. Meta-analyses revealed significant, but not robust, benefits of Tai Chi/qigong over no interventions for hypertension (systolic blood pressure: −15.55 mm Hg (95% CI: −21.16; −9.95); diastolic blood pressure: −10.66 mm Hg (95% CI: −14.90, −6.43); the homeostatic model assessment (HOMA) index (−2.86%; 95% CI: −5.35, −0.38) and fasting blood glucose (−9.6 mg/dL; 95% CI: −17.28, −1.91), and for the body mass index compared with exercise controls (−1.65 kg/m(2); 95% CI: −3.11, −0.20). Risk of bias was unclear or high for the majority of trials and domains, and heterogeneity between trials was high. Only 6 trials adequately reported safety. No recommendation for the use of Tai Chi/qigong for the prevention of stroke can be given. CONCLUSION: Although Tai Chi and qigong show some potential more robust studies are required to provide conclusive evidence on the efficacy and safety of Tai Chi and qigong for reducing major stroke risk factors.